Broadening the genetic bases of durum wheat - David J.L.; Tavaud M.; Roumet P.; Muller M.-H.; Santoni S.; Gautier S.; Holtz Y.; Ranwez V.; Ardisson M.; Poux G.; Vagne C. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
A large reservoir of genetic diversity is available in the Triticum turgidum sub-species. This diversity can be used in breeding programs but the method by which it could be introgressed in the elite durum pool is challenging once the objective is to cover the whole genome. T. turgidum accessions are usually classified in sub-species or taxa while evidence is accumulating that a more complex genetic structure can be revealed using no a priori approaches. Wild and cultivated emmers are the most diverse compartment and some cultivated emmers are strongly differentiated from naked wheats while other emmers are closer to the current durum. Recent and successive bottlenecks (in the XXth century) explain a large part of the structuration of the modern durum pool and the loss of molecular diversity. The use of T. turgidum germplasm in classical genealogical breeding may lead to some disappointments if a quick return is researched while some advances in breeding elite lines can be achieved with more recombination and selection. Evolutionary Pre-Breeding appears as a valuable alternative. Building and managing composite cross populations for a long period leads to in innovative genitors, with an enriched allelic diversity and reduced long range linkage disequilibrium.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)